2017
DOI: 10.1071/he16036
|View full text |Cite
|
Sign up to set email alerts
|

A snapshot of physical activity programs targeting Aboriginal and Torres Strait Islander people in Australia

Abstract: Issue addressed: Participation in physical activity programs can be an effective strategy to reduce chronic disease risk factors and improve broader social outcomes. Health and social outcomes are worse among Aboriginal and Torres Strait Islanders than non-Indigenous Australians, who represent an important group for culturally specific programs. The extent of current practice in physical activity programs is largely unknown. This study identifies such programs targeting this population group and describes thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 23 publications
4
32
0
1
Order By: Relevance
“…Interviewees described the positive response to IMP activities and related running participation as being linked to the community being ready to take up such an initiative. Some interviewees reflected on previous government community health initiatives that had achieved increased awareness of chronic disease . This seemed to make IMP, offering a practical way for people to prevent chronic disease, accessible and appealing extending to broader health factors such as diet and mental health, which naturally fit with holistic views of Indigenous health .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Interviewees described the positive response to IMP activities and related running participation as being linked to the community being ready to take up such an initiative. Some interviewees reflected on previous government community health initiatives that had achieved increased awareness of chronic disease . This seemed to make IMP, offering a practical way for people to prevent chronic disease, accessible and appealing extending to broader health factors such as diet and mental health, which naturally fit with holistic views of Indigenous health .…”
Section: Discussionsupporting
confidence: 88%
“…Firstly, respondents indicated that the community had experienced increased levels of readiness for healthy lifestyles in recent years. Interviewees spoke of prior whole‐of‐community initiatives that had raised awareness of chronic disease risk factors including physical activity . This awareness may have meant that when local IMP activities commenced, they were perceived by respondents as a practical way for people to embrace healthy lifestyle activities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some IMP runners have had physical and mental health challenges, few have previous running experience and are selected on their potential, not as runners, but as leaders. IMF provides training, development and support to build the potential of these young people to become aspiring role models that people in their communities can relate to in order to improve lifestyle risk factors for chronic disease3 and tackle social issues 6…”
Section: Why Does the Imf Work?mentioning
confidence: 99%